‘Seeing Touch Anew’: Clothing, Gender, and ‘The Victorian Tactile Imagination’ - Kara Tennant (19, 2014)
This article focuses upon issues of touch, gender, and perceptions of mid-Victorian 'femininity', produced as a result of 'The Victorian Tactile Imagination' conference at Birkbeck in July 2013.